2015
DOI: 10.1007/s10904-015-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Conjugating Amino Acid Schiff-Base Metal Complexes for Scavenging Superoxide Anion Radical

Abstract: Superoxide anion radical (O 2•-) is a toxic reactive oxygen species (ROS). Schiff-base metal complexes have been widely studied as synthetic antioxidants to scavenge ROS. However, it is toxic and shows poor water solubility. In this work, a kind of novel water-soluble biopolymer/metal complex conjugate (HO-SAM@BSA) was prepared by binding the 4-hydroxy-salicylaldehyde amino acid Schiffbase metal complexes (HO-SAM, M = Cu, Zn, Co) with water-soluble biopolymer bovine serum albumin (BSA). The conjugates were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…S5(b)] suggesting the conjugation of CoMSPs with BSA. This is supported by the observation of Xu et al that BSA after conjugation with cobalt shows an absorbance within 300-500 nm wavelength region and it is often weakly conjugated with cobalt atom [17]. Also, while adding DA to this BSA conjugated CoMSPs, a Fig.…”
Section: Colorimetric Sensing Of Dopaminesupporting
confidence: 73%
See 2 more Smart Citations
“…S5(b)] suggesting the conjugation of CoMSPs with BSA. This is supported by the observation of Xu et al that BSA after conjugation with cobalt shows an absorbance within 300-500 nm wavelength region and it is often weakly conjugated with cobalt atom [17]. Also, while adding DA to this BSA conjugated CoMSPs, a Fig.…”
Section: Colorimetric Sensing Of Dopaminesupporting
confidence: 73%
“…Bovine serum albumin (BSA) is a bio-ligand that is capable of stabilizing and dispersing metal hydroxides [15,16]. Xu et al used BSA to conjugate cobalt based Schiff base complexes and demonstrated them as a potential superoxide anion radical scavenger [17]. This study shows the versatility of BSA towards cobalt binding ability.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The EC 50 of BSA-Cu is 0.038±0.001 μmol L −1 , which is the lowest of all. The EC 50 of natural SOD 35 is 0.041± 0.001 μmol L −1 . The EC 50 of BSA-Cu reaches 107% compared with natural Cu, Zn-SOD.…”
Section: Superoxide Anion Radical (O •−mentioning
confidence: 96%
“…We hypothesized that RCA 120 could bind 4a, as reported for other galactose conjugates [ 35 , 53 ], and that the protein environment could modulate the activity of the catalytic center, as found for other SOD-mimetic hybrid systems [ 39 , 54 , 55 , 56 ]. The interaction between the RCA 120 and 4a complex was investigated using CD spectroscopy.…”
Section: Resultsmentioning
confidence: 97%